2012
DOI: 10.1534/genetics.111.138180
|View full text |Cite
|
Sign up to set email alerts
|

Haploidization inSaccharomyces cerevisiaeInduced by a Deficiency in Homologous Recombination

Abstract: Diploid Saccharomyes cerevisae strains lacking the RAD52 gene required for homologous recombination have a very high rate of chromosome loss. Two of four isolates subcultured ∼20 times (∼500 cell divisions) became haploid. These strains were capable of mating with wild-type haploids to produce diploid progeny capable of undergoing meiosis to produce four viable spores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Several S. cerevisiae mutantions have been identified that lead to genome reduction from diploid to haploid. For example, diploid cells with a null mutation in RAD52 (involved in strand exchange during recombination and DNA damage repair), undergo chromosome loss via sequential aneuploid transitions (87). Loss of Rad52 leads to a failure of the repair mechanism that keeps the chromosome homologs together after a double strand break (DSB).…”
Section: Mutations Underlying Ploidy Reductionmentioning
confidence: 99%
“…Several S. cerevisiae mutantions have been identified that lead to genome reduction from diploid to haploid. For example, diploid cells with a null mutation in RAD52 (involved in strand exchange during recombination and DNA damage repair), undergo chromosome loss via sequential aneuploid transitions (87). Loss of Rad52 leads to a failure of the repair mechanism that keeps the chromosome homologs together after a double strand break (DSB).…”
Section: Mutations Underlying Ploidy Reductionmentioning
confidence: 99%
“…An advanced form a-CGH-based method involves the use of single nucleotide polymorphisms (SNP) array. It is a rapid, high-resolution, and cost-effective tool used for the characterization of changes in allele diversity as well as chromosome copy number in C. albicans and also in S. cerevisiae (Song & Petes, 2012).…”
Section: A-cghmentioning
confidence: 99%
“…Saccharomyces cerevisiae strains that lack HR are very sensitive to DNA-damaging agents such as X-rays (Resnick and Martin 1976), and have a high rate of spontaneous chromosome loss (Song and Petes 2012). HR is essential for the survival of mammalian cells (Helleday 2003).…”
mentioning
confidence: 99%